PENGARUH INDEPENDENSI, AKUNTABILITAS, TEKANAN ANGGARAN WAKTU, PENGALAMAN AUDITOR DAN KEPUASAN KERJA TERHADAP KUALITAS AUDIT (Studi Empiris pada Kantor Akuntan Publik di Kota Semarang) - Siti Mirfat, 15.05.52.0278; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2019)
Public Accountants have better audit quality. Audit quality is determined by independence, accountability, time budget pressure, auditor experience, job satisfaction. This study discusses to test and analyze independence, accountability, time budget pressure, auditor experience, job satisfaction on audit quality (Empirical Study of Public Accounting Firms in the City of Semarang). The population used in this study was the auditor who worked in the KAP in Semarang City. The sampling method used is convenience sampling, which is the selection of samples based on convenience, so that they have the freedom to choose the fastest and easiest sample. In this research the variable used is audit quality, while the independent variable consists of independence, accountability, time budget pressure, auditor experience, job satisfaction. The data analysis techniques use multiple linier regression models. The results of this study indicate the independence and experience of auditors does not show a positive significant effect on audit quality. Accountability, time budget pressure, positive positive job satisfaction on audit quality.